Teenagers Tell Better Stories After Improvisational Theater Courses - Blonde, Manon; Mortelier, Frédérique; Bourdin, Béatrice; Hainselin, Mathieu (Frontiers in Psychology, 2021)
Improvisational theater (improv) is a booming theatrical practice, applying in many fields (teaching, medicine or entrepreneurship). Its effects on cognitive and behavioral processes are beginning to be demonstrated, despite scientific publications that are still rare and particularly about language. This study aimed to evaluate the effects of improv on adolescent narrative skills. Twenty-seven middle school students were recruited and divided into two groups: an IMPRO group (n = 13), composed of novice and intermediate improvisers, and a CONTROLE group (n = 14), composed of middle school students doing theater. The evaluation took place in two experimental times spaces three months apart (11 sessions). It consisted in the creation of a written narrative resulting from previously observed images. The analysis of this story was carried out on the basis of quantitative criteria (coherence, cohesion, lexicon and syntax), according to the methodologies of PELEA and EVALEO. We showed an effect of the improv on coherence, which suggests that the practice of improv introduces teenagers to improve the narrative skills and the planification of a story, unlike written theater.